Impact of Post-Stroke Cognitive Impairment with No Dementia on Health-Related Quality of Life - Jung Hyun Park; Beom Joon Kim; Hee-Joon Bae; Jisung Lee; Juneyoung Lee; Moon-Ku Han; Kyung Yoon O; Seong Ho Park; Yeonwook Kang; Kyung-Ho Yu; Byung-Chul Lee (Journal of Stroke, 2013)
Background and PurposeHealth-related quality of life (HRQoL) is a multidimensional concept that signifies a subjective evaluation of perceived health; hence, it has gained wide acceptance in geriatrics. However, its application has not been tested in patients with post-stroke cognitive impairment with no dementia (PSCIND). We investigated whether PSCIND interferes with HRQoL measured by EQ-5D, compared the findings to those of healthy people with normal cognition, and evaluated the influence of each cognitive domain on this score.MethodsIn total, 1,528 subjects were identified who had undergone neuropsychological assessment using the 60-min protocol of the Korean version of Vascular Cognitive Impairment Harmonization Standards, EQ-5D, and magnetic resonance imaging at the stroke prevention clinic. Fifty PSCIND patients were matched to 50 post-stroke dementia (PSD) patients and 50 normal age- (±3 years) and sex-matched controls. The effects of PSCIND, PSD, and control groups upon the EQ-5Dindex score were tested by generalized estimating equation modeling.ResultsEstimated means±standard errors of EQ-5Dindex scores were as follows: 0.94±0.06 (control group), 0.86±0.08 (PSCIND group), and 0.61±0.32 (PSD group); and the difference among the three groups was statistically significant (P<0.0001). Pairwise comparisons showed that EQ-5Dindex scores in the PSCIND group differed from those in the PSD and control groups (both P<0.01). No cognitive domain was specifically associated with EQ-5Dindex scores after adjusting for functional status.ConclusionsThis study shows that PSCIND may interfere with the quality of life in stroke victims.